New Hope for a “Cursed” Crop? Understanding Stakeholder Attitudes to Plant Molecular Farming With Modified Tobacco in Europe - Menary, Jonathan; Amato, Mario; Sanchez, Andrés Cid; Hobbs, Matthew; Pacho, Agata; Fuller, Sebastian S. (Frontiers in Plant Science, 2020)
Plant molecular farming with tobacco could provide a sustainable and cheap platform for the production of high-value proteins for medical use. It could also offer European tobacco farmers an alternative, healthful end use for their crop. New plant breeding techniques offer a means of quickly and precisely optimising molecular farming platforms for this purpose. However, there has been little empirical research focussing on the barriers and facilitators of these technologies in the agricultural sphere. Here, we explore key stakeholder perceptions towards this combination of technologies, exploring their understanding of risk and opportunity. We interviewed N=24 key stakeholders – tobacco farmers, agronomists, policymakers and researchers – in three tobacco-growing areas of Spain and Italy. Our findings demonstrate these stakeholders have a favourable attitude towards plant molecular farming with tobacco due to its beneficial medical purpose and the opportunity it provides farmers to continue growing tobacco in a declining European market. Tobacco producers also reported favourable views towards new plant breeding techniques, though for some this was contingent on their use for non-food crops like tobacco. Most stakeholders’ concerns are economic in nature, such as potential profitability and demands for new agronomic practices or infrastructure. Tobacco producer associations were thought to be important facilitators for future plant molecular farming scale-up. The attitude towards these technologies by smoking tobacco companies is, however, unknown and constitutes a potential risk to the development of plant molecular farming.